Graduation and study of the hadith (the reason for Ali's (may God be pleased with him) absence from the Prophet (peace and blessings be upon him) on the day of the migration) in the interpretation of (Husnul-Bayan) by al-Balisani (Part Three) - عبدالله, أ. م. د. كامل عزيز عبدالله; Ahmed, Shakhwan Jawad Ahmed (Sulaimani Journal for Humanities, 2025)
God, Glory be to Him, God Almighty, has been gracious to His servants by sending down the Qur’an to them and explaining it and clarifying the Sunnah of the Prophet, so that they may be a religion, a law, and a reference in understanding the intent of God Almighty and the intent of His Messenger, may God bless him and grant him peace. One of the greatest blessings upon a Muslim is the blessing of success in seeking legal knowledge from the Qur’an and Sunnah in accordance with the understanding of the righteous predecessors. Whoever follows other than the path of the righteous predecessors in understanding the texts has gone astray and lost. Every Muslim, in addition to the seeker of knowledge, must devote himself to adhering to the Sunnah, following the tradition, and following the path of the righteous predecessors, for they are those whom God Almighty has chosen and approved of to convey His religion, and who carried the trust of knowledge, so they carried out it to the fullest extent and in the best condition. Part of God’s preservation of this religion was that he made excellent scholars subservient to it, as they collected, codified, and disseminated this religion. One of the aspects that they paid attention to in serving this religion is their interpretation of the Holy Qur’an with its well-known rules, especially their interpretation of the Holy Qur’an with the Prophet’s hadiths and narrated traces.
Keywords: The Holy Quran; interpretation; Sheikh Muhammad Taha Al Balisani; Prophetic hadiths; narrated narrations